INTRODUCING A MATHEMATICAL MODEL FOR BONE METASTASES CONTROL - nikbakht, maryam (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper after investigating a specific drug to prevent progressing of bone metastases; a new mathematical model is introduced for affection of this drug. Bone metastases (secondary tumor) occurs when cancer cells spread from their original site to a bone. Some types of cancer such as breast cancer particularly spread to a bone. The aim of this paper is to express an optimal control model for drug treatment that minimizes the amount of used drug while the size of secondary tumor should be less as possible. The model is described as a nonlinear partial differential equations.